Analisis 5C pada Bank di Gresik - Emilda Fajriyati; Rahmat Agus Santoso (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the application of the 5C principles (Character, Capacity, Capital, Collateral, and Condition of Economy) in the credit granting process at bank in gresik. The research employs a qualitative approach using a case study method. Data were collected through interviews with credit officers and related parties, supported by documentation and observation of credit procedures. The results indicate that bank in gresik has formally implemented the 5C principles in accordance with established procedures. However, their implementation has not been carried out optimally and evenly. The assessment of Character and Capacity tends to rely on subjective judgment, Capital analysis has not been prioritized, while Collateral becomes the dominant factor in credit approval decisions. In addition, the analysis of economic conditions has not been conducted comprehensively. These conditions contribute to the emergence of credit risk and the increase in non-performing loans. Therefore, strengthening the balanced application of the 5C principles is essential to improve credit quality.